Affecting Consonance, Striving for Dominance: Scholarship and Politics at the Congresses of Byzantine Studies in the Balkans, 1924-1934 - Ignjatovic, Aleksandar (Journal of Balkan and Near Eastern studies, 2019)
Despite the rapid development of Byzantine studies in the Balkans, Byzantium has remained a controversial and highly politicized subject. Its historical status and ideological significance are ambiguous, making it a topic germane to both scholarship and politics. This was particularly evident at the first four International Congresses of Byzantine Studies held between 1924 and 1934 in Bucharest, Belgrade, Athens and Sofia. This article examines the ideological frameworks and political implications of the congresses as a conspicuous example of the symbiotic nexus between scholarship and politics developed in the precarious geopolitical context of the post-Versailles Balkans. What this article shows is that Byzantium was simultaneously seen as a transnational legacy and exclusive national heritage, which has remained key to its ideological instrumentality until today.